2012
DOI: 10.1007/s10875-012-9707-y
|View full text |Cite
|
Sign up to set email alerts
|

Tyrphostin AG490 Agent Modestly but Significantly Prevents Onset of Type 1 in NOD Mouse; Implication of Immunologic and Metabolic Effects of a Jak-Stat Pathway Inhibitor

Abstract: Previously, we have reported that the Jak-Stat signaling pathway is defective in NOD mice. In this study, prediabetic female NOD mice (4 weeks) were treated by intraperitoneal injection either with AG490 or DMSO three times per week for 4 consecutive weeks, followed by once a week for an additional 6 weeks. The onset of diabetes was attenuated in NOD mice treated with AG490 relative to DMSO treated control mice (p < 0.02). From an immunological standpoint, AG490 induced the expression of Foxp3 in CD4(+)CD25(-)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…administration of Tyrphostin AG490 had no effect on body weight gain or loss; however, blood glucose values were significantly lower in Tyrphostin AG490 treated NOD mice at week 8 (p=0.0021, n=15, figure 1) when compared with DMSO treated mice (n=14), suggesting metabolic effects of this compound on glucose metabolism. As noted previously, we recently demonstrated successful prevention and reversal of T1D in NOD mice (Davoodi-Semiromi et al 2012a; Davoodi-Semiromi et al 2007b), opening the possibility that the Jak-Stat signaling pathway has a negative effect on glucose metabolism in situations of ongoing inflammation; yet, this notion required investigation.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…administration of Tyrphostin AG490 had no effect on body weight gain or loss; however, blood glucose values were significantly lower in Tyrphostin AG490 treated NOD mice at week 8 (p=0.0021, n=15, figure 1) when compared with DMSO treated mice (n=14), suggesting metabolic effects of this compound on glucose metabolism. As noted previously, we recently demonstrated successful prevention and reversal of T1D in NOD mice (Davoodi-Semiromi et al 2012a; Davoodi-Semiromi et al 2007b), opening the possibility that the Jak-Stat signaling pathway has a negative effect on glucose metabolism in situations of ongoing inflammation; yet, this notion required investigation.…”
mentioning
confidence: 75%
“…With respect to specific effects of Tyrphostin AG 490 on the immune response, it has been noted to block IL-12 mediated T-cell proliferation, inhibit phosphorylation of Stat3, decrease IFN-γ production mediated by IL-12 (Bright et al 1999), and inhibit the differentiation of antigen-specific Th1 cells in vivo (Changelian et al 2003). Recently, we demonstrated that in vivo administration of Tyrphostin AG 490 prevents and reverses T1D in NOD mouse (Davoodi-Semiromi et al 2012a; Davoodi-Semiromi et al 2012b), suggesting that this drug possess immunomodulating properties; however, potential metabolic effects (i.e., those separate of immunological in nature) of this compound have not been desribed. Compelling evidence demonstrates that the Jak-Stat signaling pathway plays a critcal role in adipocyte development and function (Baugh, Jr. et al 2007; Coulter and Stephens 2006; Floyd et al 2007; Richard and Stephens 2011; Stewart et al 2011; White et al 2007; White and Stephens 2010a; White and Stephens 2010b; Zhang et al 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, RTKI treatment also enhances insulin-independent glucose metabolism in peripheral tissues. In this regard, recent studies have shown that JAK-STAT inhibitors increased peroxisome proliferator–activated receptor-γ (PPAR-γ), a critical regulator of fatty acid storage and glucose metabolism, expression in adipocytes and immune cells (46). …”
Section: Discussionmentioning
confidence: 99%
“…The experiments were conducted as follows (n=8): 1) Sham group: normal rats were only subjected to the sham operation; 2) Sham+BBR group: the rats were orally treated with BBR (in 0.5% CMC-Na solution, 200 mg·kg -1 ·d -1 , 2 weeks) and then subjected to the sham operation; 3) Sham+AG group: the rats were treated with AG490 (5 mg·kg -1 ·d -1 , ip, 3 days before MI/R operation, 20 mg/kg, 10 min after the beginning of the operation) and then subjected to the sham operation. The doses of BBR and AG490 were selected based on previous reports [24][25][26][27] . Second, we tested the effects of BBR and AG490 on the MI/R-injured rat hearts.…”
mentioning
confidence: 99%